In personam jurisdiction in internet transactions (2010)
The fundamental nature of jurisdiction cannot be overlooked in giving effectiveness to judgments or orders given by a court, as no court will want to act in vain. Power to exercise jurisdiction in a matter presupposes a boundary or territorial limit within which such a power can be exercised. In civil matters under the common law system the traditional basis of in personam jurisdiction is the service of the process(es) of a court on the defendant. The Internet, by nature, has no definite boundaries, as it has no physical sitting place but only exists or resides in a virtual cosmos, and its ubiquitous nature makes it to be present everywhere, thus accessible in different jurisdictions. The nature of man in exploring beyond borders to make business gains and to acquire necessities has been made possible and easier through the internet. There is an undisputable tendency that many states have attempted to apply tcrws traditionally made for transactions that take place in the physical world to those that are executable on the internet. Hence these states will always want to assume jurisdiction in internet transactions on the basis of their traditional lerws, in which case such laws are twisted out of shape to heed this call. The basis upon which jurisdiction can be assumed in internet transactions is therefore explored in this work with a view of suggesting viable solutions to the evasive nature of the in personam jurisdictional concept in the internet.